Sulphide Petrology and Contribution of Subducted Sulphur in Diamondiferous Garnet-Bearing Pyroxenites from Beni Bousera (Northern Morocco). (26th October 2021) - Lorand, Jean-Pierre; Pont, Sylvain; Labidi, Jabrane; Cartigny, Pierre; El Atrassi, Fatima
Abstract: This paper explores the unusual sulphide–graphite association of a selection of Beni Bousera garnet clinopyroxenites that initially equilibrated within the diamond stability field. Compared with common graphite-free garnet pyroxenites analysed so far, these rocks display tenfold S enrichment with concentrations up to 5550 μg g –1 . Fe–Ni–Cu sulphides (up to 1·5 wt%) consist of large (up to 3 mm across), low-Ni pyrrrhotite (<0·1 wt% Ni) of troilite composition, along with volumetrically minor chalcopyrite and pentlandite. Such assemblages are interpreted as low-temperature (<100 °C) subsolidus exsolution products from homogeneous monosulphide solid solution. Troilite compositions of the pyrrhotite indicate strongly reducing conditions that are estimated to be slightly above the iron–wüstite (IW) buffer. Bulk-sulphide compositions are closer to the FeS end-member (i.e. Cu- and Ni-depleted) than other sulphide occurrences in mantle-derived pyroxenites described so far. Moreover, troilite contains trace metal microphases (Pb and Ag tellurides, molybdenite) that have never been reported before from mantle-derived garnet pyroxenites but occur in diamond-hosted eclogitic sulphide inclusions. Beni Bousera sulphides also show strong similarities to diamond-hosted sulphide inclusions of eclogitic affinity for a wide range of chalcophile–siderophile trace element contents. In view of the widespread molybdenite exsolution, coupled with Mo and S/Se/Te systematics of sulphide compositions (7872 < S/Se < 19 776; 15 < Se/Te < 31), black-shale pyrite is a potential sedimentary component to contribute to the petrogenesis of Beni Bousera garnet clinopyroxenites. Black shales would have recycled along with cumulates from the oceanic crust in the mantle source of Beni Bousera pyroxenites. Pyrite underwent desulfidation and replacement by troilite during subduction and prograde metamorphism, releasing its fluid-mobile elements (As, Sb, Pb) while suffering minimum S loss because of the strongly reduced conditions. Taken as a whole, our body of data supports a common origin for carbon (−27 ‰ < δ 13 C < −17 ‰) and sulphur and concomitant formation of diamond and sulphides. Both elements were delivered by an extraneous sedimentary component mixed with the altered oceanic crust rocks that was involved in the genesis of Beni Bousera garnet pyroxenites, prior to a Proterozoic partial melting event.